PKC isoforms activate LRRK1 kinase by phosphorylating conserved residues (Ser1064, Ser1074 and Thr1075) within the CORB GTPase domain. Issue 18 (30th September 2022) - Malik, Asad U.; Karapetsas, Athanasios; Nirujogi, Raja S.; Chatterjee, Deep; Phung, Toan K.; Wightman, Melanie; Gourlay, Robert; Morrice, Nick; Mathea, Sebastian; Knapp, Stefan; Alessi, Dario R.
Abstract : Leucine-rich-repeat-kinase 1 (LRRK1) and its homolog LRRK2 are multidomain kinases possessing a ROC-CORA -CORB containing GTPase domain and phosphorylate distinct Rab proteins. LRRK1 loss of function mutations cause the bone disorder osteosclerotic metaphyseal dysplasia, whereas LRRK2 missense mutations that enhance kinase activity cause Parkinson's disease. Previous work suggested that LRRK1 but not LRRK2, is activated via a Protein Kinase C (PKC)-dependent mechanism. Here we demonstrate that phosphorylation and activation of LRRK1 in HEK293 cells is blocked by PKC inhibitors including LXS-196 (Darovasertib), a compound that has entered clinical trials. We show multiple PKC isoforms phosphorylate and activate recombinant LRRK1 in a manner reversed by phosphatase treatment. PKCα unexpectedly does not activate LRRK1 by phosphorylating the kinase domain, but instead phosphorylates a cluster of conserved residues (Ser1064, Ser1074 and Thr1075) located within a region of the CORB domain of the GTPase domain. These residues are positioned at the equivalent region of the LRRK2 DK helix reported to stabilize the kinase domain αC-helix in the active conformation. Thr1075 represents an optimal PKC site phosphorylation motif and its mutation to Ala, blocked PKC-mediated activation of LRRK1. A triple Glu mutation of Ser1064/Ser1074/Thr1075 to mimic phosphorylation, enhanced LRRK1 kinase activity ∼3-fold. From analysis of available structures, we postulate that phosphorylation of Ser1064, Ser1074 and Thr1075 activates LRRK1 by promoting interaction and stabilization of the αC-helix on the kinase domain. This study provides new fundamental insights into the mechanism controlling LRRK1 activity and reveals a novel unexpected activation mechanism.